Regulating virtual currencies - Eduard Hofert (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2019)
Distributed ledger technology especially in the form of publicly coordinated validation networks such as Ethereum and Bitcoin with their own monetary circles provide for a revealing litmus test for current financial regulatory schemes. The paper highlights the interrelation between distributed coordination and the emission of virtual currency to make sense of the function of the new monetary phenomenon. It then argues for the regulation of financial services on the ground of the technology to ensure integrity standards. In this respect, it is useful to gear the development of a regulatory scheme towards the existing financial regulatory principles. However, future measures of the regulators must take the distributed nature of the platforms into account by relying on a "regulated self-regulation" of the community. Finally, the article focuses on the shortcomings of the current EU regulatory regimes, especially the regulation frameworks regarding financial services, payment services and electronic money.
urn:nbn:de:hebis:30:3-488053
Keywords: 330